Pengaruh Kompetensi Pustakawan Dan Kualitas Pelayanan Keanggotaan Terhadap Kepuasan Pemustaka Di UPT Perpustakaan Proklamator Bung Karno - Maharani, Ellys Sri; Swasono, Edy (Otonomi, 2024)
Based on Undang-Undang RI Number 43 of 2007 concerning libraries, the ultimate goal of library services is user satisfaction. Every development carried out by the library is aimed at the interests of users so that user satisfaction can be achieved. The purpose of this study is to analyze the influence of the significance of librarians' competence and the quality of membership services on user satisfaction. In this study, the researcher used a descriptive method with a quantitative approach using a sampling of 100 people. The data collection technique uses a questionnaire. The test in this study uses multiple regression analysis. The results of this study explain that the librarian competency variable has no effect on user satisfaction; the quality of membership services affects user satisfaction; while together the competence of librarians and the quality of membership services affect the satisfaction of users at the UPT Perpustakaan Proklamator Bung Karno.